On-orbit NOAA-20 VIIRS solar diffuser bidirectional reflectance distribution function and screen transmittance characterization using yaw manoeuvres and regular on-orbit SDSM data. Issue 17 (1st September 2020) - Choi, Taeyoung; Shao, Xi; Blonski, Slawomir; Cao, Changyong
ABSTRACT: On-orbit radiometric calibration of the Visible Infrared Imaging Radiometer Suite (VIIRS) sensor onboard the National Oceanic and Atmospheric Administration's (NOAA) NOAA-20 satellite is dependent on Solar Diffuser (SD) and Solar Diffuser Stability Monitor (SDSM) observations for the Reflective Solar Bands (RSBs). The time-dependent degradation of the SD Bidirectional Reflectance Distribution Function (BRDF) (called H -factor) is measured by the SDSM. To reduce direct illumination from the Sun, SD and SDSM have two independent screens called SD Screen (SDS) and SDSM Sun view screen. Once the instrument is on-orbit, the product of the SD BRDF and SDS transmittance can only be measured by VIIRS and SDSM detectors through the Rotating Telescope Assembly (RTA) and SDSM SD viewport, respectively. Using pre-launch parameter tables, the initial H -factor trends showed abnormal oscillations. To validate the functionality of the pre-launch tables, the NOAA-20 VIIRS spacecraft performed 15 yaw manoeuvres on 25 January and 26 January 2018 as a part of post-launch tests. During the yaw manoeuvres, on-orbit SD and SDSM data were collected and used to characterize the SD screen transmittance functions with BRDFs and the SDSM Sun view screen transmittance functions. On-orbit estimated SD/SDSM BRDFs and SDSM Sun screen transmittance functions showed some differences from the pre-launch version, especially with the SDSM Sun view screen transmittance function. This problem was not resolved by applying the initial yaw manoeuvre-derived table. As an alternative approach, NOAA VIIRS team applied a methodology to add fine features in the SDSM Sun transmittance function from the one-year regular on-orbit SDSM collections to cover a full operational range of the solar azimuth angle in the SDSM Sun viewport. After applying additional SDSM detector gain corrections, the yaw manoeuvre and on-orbit regular SDSM data points are aligned that reduced abnormally large degradations in SDSM detector 6, 7, and 8. Finally, 1% level H -factor oscillations are reduced to 0.2% level. Corresponding SD F -factors, scaling calibration coefficients, are calculated and deliver to the NOAA's Interface Data Processing Segment (IDPS) to generate the official VIIRS Science Data Record (SDR) products.